Competitiveness and Determinants of Indonesian Plywood Export - Leo Rio Ependi Malau; Raissa Anjani; Nur Arifatul Ulya; Edwin Martin (Jurnal Sylva Lestari, 2022)
Since 1998, Indonesia has been the largest plywood exporter in the world. However, at this time, Indonesia's position no longer dominates; even the plywood export volume and value tend to decline. This condition is determined by many factors and is closely related to the competitiveness concept. Therefore, this study aimed to analyze the competitiveness, determinants, and export potential of Indonesian plywood. This study uses panel data from 11 major trading partner countries from 2004 to 2020. The data analysis method used in this study includes Revealed Comparative Advantage (RCA), gravity model, and trade potential analysis. The results show that Indonesian plywood has strong competitiveness in 11 major trading partner countries with a positive growth trend. The estimation of the gravity model shows that the importer population, economic distance, and the RCA index have a positive effect on Indonesian plywood exports. In contrast, Indonesia's real GDP, importers' GDP, exchange rates, and export prices are negatively affected. The population of importers is the most significant elasticity variable. Indonesia still has the potential to expand in 11 major trading partner countries because of the plywood under-trade current condition. So, development efforts on plywood exports should be aimed at under-trade countries and large populations. Keywords: export, gravity model, panel data, Revealed Comparative Advantage, trade potential ratio